Coronary Artery Disease is More Severe in Patients with Non-Alcoholic Steatohepatitis than Fatty Liver - Niikura, Toshihiro (Diagnostics (Basel), 2020)
Non-alcoholic fatty liver disease (NAFLD) is associated with a higher risk of atherosclerotic disease. However, the relationships between the severity of coronary atherosclerosis and pathologic findings in patients with NAFLD remain unknown. We aimed to characterize the coronary artery lesions in patients with NAFLD using coronary computed tomography angiography (CCTA). Overall, 101 patients with liver biopsy-proven NAFLD who had chest pain or electrocardiographic abnormalities underwent CCTA. Coronary artery lesions, including coronary artery stenosis (CAS), calcium score (CACS, Agatston score), and coronary artery non-calcified plaque were assessed using multi-slice CT. Multivariate analysis showed that age, smoking status, prevalence of dyslipidemia (DLP) and non-alcoholic steatohepatitis (NASH), and stage of fibrosis were independent risk factors for CAS. Age, and the prevalence of DM and DLP, were independent risk factors for CACS, and the prevalence of NASH tended to be an independent risk factor. In addition, the prevalence of DLP and NASH were independent risk factors for non-calcified plaques. Coronary artery lesions are more common in patients with NASH than in those with non-alcoholic fatty liver, suggesting a higher risk in patients with NASH. Therefore, patients with NASH should be closely followed, with particular vigilance for coronary artery diseases.